Engineering immunomodulatory hydrogels and cell-laden systems towards bone regeneration - Nadine, Sara (2022)
The well-known synergetic interplay between the skeletal and immune systems has changed the design of advanced bone tissue engineering strategies. The immune system is essential during the bone lifetime, with macrophages playing multiple roles in bone healing and biomaterial integration. If in the past, the most valuable aspect of implants was to avoid immune responses of the host, nowadays, it is well-established how important are the crosstalks between immune cells and bone-engineered niches for an efficient regenerative process to occur. For that, it is essential to recapitulate the multiphenotypic cellular environment of bone tissue when designing new approaches. Indeed, the lack of osteoimmunomodulatory knowledge may be the explanation for the poor translation of biomaterials into clinical practice. Thus, smarter hydrogels incorporating immunomodulatory bioactive factors, stem cells, and immune cells are being proposed to develop a new generation of bone tissue engineering strategies. This review highlights the power of immune cells to upgrade the development of innovative engineered strategies, mainly focusing on orthopaedic and dental applications.